Numerical investigation of different transverse Rib shapes on thermal convection in a channel filled with nanofluid - Fatima-Zahra Barhdadi; Ikrame Jamal; Kamal Amghar; Salah Daoudi; Réda Yahiaoui; Kamal Ghoumid (International Journal of Thermofluids)
With the growing interest in energy optimization, corrugated surfaces are arguably an excellent choice, finding applications in areas as diverse as heat exchangers, automobiles, building energy efficiency, and chemical reactors. However, due to the poor thermal properties of conventional fluids, heat transfer is limited. The introduction of nanoparticles into fluids is a promising solution to improve their thermal performance. This paper does a detailed numerical analysis of how different factors affect the forced convection heat transfer in a two-dimensional ribed channel. The shape of the ribs is one of the factors that are looked at, along with some new parameters like e/H, which is the ratio of rib height to channel height, and L2/P, which is the test section to the pitch between the ribs. The aim is to determine the optimum geometry that maximizes the Nusselt number while minimizing the pressure drop. The study also examines the effects of nanoparticle type and concentration on heat transfer and fluid flow characteristics. To this end, the continuity, momentum, and energy equations were solved with the finite volume method using the SIMPLE scheme with the k-ε turbulence model at different Reynolds numbers ranging from 4000 – 14,000. The results indicate that triangular ribs with ratios e/H = 0.15 and L2/P = 4 increase the Nusselt number by 63.3 % while reducing the pressure drop by 22 % compared with the other cases. The improvement in heat transfer in the water-SiO2 case was the greatest compared with the other nanofluids tested. Particle size fraction and Reynolds number increased the Nusselt number in ribbed channels by 20.7 % compared with water.